2013
DOI: 10.22364/mhd.49.1-2.18
|View full text |Cite
|
Sign up to set email alerts
|

Convection in a vertical layer of stratified magnetic fluid

Abstract: Infrared camera visualisation of convective flows in differentially heated vertical layers with the height-to-thickness ratios of 30 and 62.5 was used to demonstrate the influence of concentration stratification caused by gravitational sedimentation of magnetic particles and aggregates on the structure of convective motion. It is found that when a density gradient is established in an isothermal layer over a period of several weeks prior to the experiment, cellular structures occur after the heating begins. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“…A series of earlier experiments [26,29,30] conducted in a thin disk-shaped vertical cavity of aspect ratio (diameter to thickness) 21.4 showed that magnetoconvection can play a dominant role in a vertical layer geometry. The resulting convection patterns were found to be drastically different from those expected to exist in a differentially heated vertical layer of nonmagnetic fluid, due to thermogravitational instability.…”
Section: Introductionmentioning
confidence: 99%
“…A series of earlier experiments [26,29,30] conducted in a thin disk-shaped vertical cavity of aspect ratio (diameter to thickness) 21.4 showed that magnetoconvection can play a dominant role in a vertical layer geometry. The resulting convection patterns were found to be drastically different from those expected to exist in a differentially heated vertical layer of nonmagnetic fluid, due to thermogravitational instability.…”
Section: Introductionmentioning
confidence: 99%
“…Flow stabilization is influenced by the kind of fluid, which is represented by viscosity and, as a result, the fluid's Prandtl number. We choose the Prandtl number Pr as 27.5 and let χ = χ = 3 (for linear magnetization) as well as the unequal values such as χ = 3, χ = 5 (for nonlinear magnetization regime) as in the experiment of (Bozhko et al 2013). In agreement with (Rahman & Suslov, 2015), we have also chosen lower values of χ = 0.5 and 1.5, as well as χ = 1.5 and 2.5, which are magnetic states that are close to saturation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Данная постановка соответствует ситуации, в которой сосуд длительное время находился в горизонтальном положении, а затем был повернут на 90 • [17]. Во втором случае рассматривалась более сложная геометрия (рис.…”
Section: постановка задачиunclassified
“…Для ускорения формирования экспоненциального профиля в узком канале жидкость может отстаиваться в горизонтальном положении, а затем емкость приводится в вертикальное положение [17] (рис. 1).…”
Section: Introductionunclassified